Efektivitas Implementasi Model Problem Based Learning (PBL), Blended Learning (BL), Serta Integrasinya Terhadap Hasil Belajar Ditinjau Dari Kemampuan Mengevaluasi Dan Kreativitas Siswa - PRANOTO, EDI; SUDARISMAN, SUCIATI; SUNARNO, WIDHA (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
The purpose of this study was to determine the effect of Problem Based Learning (PBL), Blended Learning (BL) models, and the Integration of BL-PBL, capability of evaluating and creativity toward student’s achievement. This experimental research was carried out in September to December 2013. The populations of research were all students in grade XI of SMA Negeri l Pati Academic Year 2013/2014 that consists of 262 students divided into eight study groups. The sample of research was consisted of three study groups; they were XI-IPA2, XI-IPA4 and XI-IPA6 determined by random cluster sampling technique. XI-IPA2 study group used BL model, XI-IPA4 study group used PBL model, and XI-IPA6 study group used the Integration of BL-PBL models. The data was collected by using the instrument of cognitive test, and questionnaires of affective, psychomotor, capability of evaluating and creativity. The data then was analyzed by using three-ways ANAVA with 3x2x2 factorial design with signification 5%, and it then was continued by using Scheffe test if there was interaction. Based on the data analysis, it can be concluded that: 1) There was no difference of effect of BL, PBL, and the Integration of BL-PBL models toward student’s cognitive, affective and psychomotor achievements; 2) There was difference of effect of capability of evaluating toward student’s cognitive, affective and psychomotor achievements; 3) There was effect of creativity toward student’s cognitive, affective and psychomotor achievements; 4) There was no interaction between BL, PBL, and the Integration of BL-PBL models with the capability of evaluating toward student’s cognitive, affective and psychomotor achievements; 5) There was interaction between BL, PBL models, and the Integration of BL-PBL with the creativity toward student’s cognitive, affective and psychomotor achievements; 6) There was interaction between capability of evaluating and creativity toward student’s cognitive, affective and psychomotor achievements; 7) There was no interaction between BL, PBL models, and the Integration of BL-PBL, capability of evaluating and creativity toward student’s cognitive, affective and psychomotor achievements.